An empirical study on paths of creating harmonious corporate culture - Lianke Song; Bernt Mayer (Hochschule für angewandte Wissenschaften Amberg-Weiden (HAW), 2010)
Creating harmonious corporate culture has been a new issue in present day society. Many scholars studied paths of creating harmonious corporate culture but nobody used quantitative methods. This study collected 205 valid questionnaires and held 12 study meetings to find the paths of creating harmonious corporate culture. Authors identified 62 analysis units and 27 small categories and 4 categories. All paths were assigned to 4 categories as spiritual culture, institutional culture, behavioral culture and material culture. This paper discussed paths of creating harmonious corporate culture in order to seek out which paths were perceived and received by most people. The results of this paper are useful to entrepreneurs who want to build harmonious corporate culture. – – Das Schaffen von harmonischen Unternehmenskulturen ist in der Öffentlichkeit ein neues Thema geworden. Viele Gelehrte eruierten Wege hierfür, aber niemand setzte quantitative Methoden ein. Die vorliegende Studie sammelte 205 Fragebögen und hielt 12 Meetings ab, um Wege der Entwicklung einer harmonischen Unternehmenskultur zu finden. Die Autoren identifizierten 62 Analyse-Einheiten, 27 Unterkategorien und 4 Hauptkategorien. Alle Wege wurden den 4 Hauptkategorien Spirituelle Kultur, Institutionale Kultur, Verhaltenskultur und Materielle Kultur zugeordnet. Diese Arbeit diskutiert Wege der Entwicklung harmonischer Unternehmenskulturen, um heraus zu finden, welche Wege von den meisten Menschen wahrgenommen und angenommen wurden. Die Ergebnisse dieser Arbeit können für Unternehmer nützlich sein, die eine harmonische Unternehmenskultur aufbauen wollen.
Keywords: L26; M12; M14; 330; Harmonious corporate culture; Harmony; Corporate culture